1990
DOI: 10.1093/oxfordjournals.aje.a115746
|View full text |Cite
|
Sign up to set email alerts
|

Vasectomy and the Risk of Prostate Cancer

Abstract: An unexpected association between history of vasectomy and increased risk of prostate cancer emerged when multiple comparisons were carried out in data collected from 1976-1988 in a US hospital-based case-control study of many diseases and exposures. The association was assessed in detail in these data, in a comparison of 220 men with first episodes of prostate cancer with 571 noncancer controls and 960 cancer controls. The age-adjusted relative risk of prostate cancer was 5.3 (95% confidence interval 2.7-10) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(26 citation statements)
references
References 0 publications
0
24
0
2
Order By: Relevance
“…Well documented are the development of sperm antibody response in vasectomized men and animals (2, 3), and autoimmune orchitis in vasectomized animals (4). More alarming is a positive statistical correlation with prostate cancer in long-term vasectomized humans (5,6). Although not confirmed (4), the initial findings have continued to influence clinical decisions regarding vasectomy (7).…”
Section: Foxp3mentioning
confidence: 99%
“…Well documented are the development of sperm antibody response in vasectomized men and animals (2, 3), and autoimmune orchitis in vasectomized animals (4). More alarming is a positive statistical correlation with prostate cancer in long-term vasectomized humans (5,6). Although not confirmed (4), the initial findings have continued to influence clinical decisions regarding vasectomy (7).…”
Section: Foxp3mentioning
confidence: 99%
“…7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 Potential biological mechanisms supporting an association between vasectomy and incident prostate cancer include increases in androgen levels, which are hypothesised to increase the risk of prostate cancer,31 and impaired secretory function of the prostate, which might prolong exposure of the prostate to carcinogenic factors 11. Although some studies have shown an increase in serum dihydrotestosterone and testosterone after vasectomy,32 33 34 others have found no statistically significant change in androgen levels 35…”
Section: Introductionmentioning
confidence: 99%
“…25 It is possible that vasectomized men were more likely to participate in prostate cancer screening during these years because of a perceived risk from vasectomy. Previous case-control studies 18,19 have been criticized because of low vasectomy prevalence rates among controls. 25±27 If there is selection bias in the current study, it should con®rm our ®ndings more conclusively.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,17,21±23 One report of a positive association 18 later reversed its ®ndings. 28 Length of time between vasectomy and a diagnosis of prostate cancer has been more consistently reported as being associated with prostate cancer than vasectomy alone.…”
Section: Introductionmentioning
confidence: 99%